Vocational Education and Training for Farmers and Other Actors in the Agri-Food Value Chain in Africa - Oliver K. Kirui; Marta Kozicka (University of Bonn, Center for Development Research (ZEF), 2018)
The study analyzes the current state of Agricultural Technical and Vocational Education and Training (ATVET) in Africa and presents its challenges and opportunities. A review of the ATVET in selected Sub- Saharan Africa countries shows that there are far too few training opportunities for young people and that often, the training offered does not match the needs of the private sector and of local administrations. ATVET trainings focus primarily on production skills and on producers themselves with too little practical training. ATVET needs to be adapted to the context of increasingly commercial and technical 21st century agricultural systems. We use the German dual ATVET system as a case study for best practices. The study concludes that an effective reform of ATVET in Africa would require policies and initiatives that tackle the general challenges as well as taking advantage of country-specific opportunities.
Keywords: 330; Agricultural technical and vocational education and training (ATVET); agri-food system; dualsystem; vocational schools; value chains; Africa